2003
DOI: 10.1007/s00209-002-0482-y
|View full text |Cite
|
Sign up to set email alerts
|

Normal C R structures on S3

Abstract: We classify the normal CR structures on S 3 and their automorphism groups. Together with [2], this closes the classification of normal CR structures on compact 3-manifolds. We give a criterion to compare two normal CR structures, and we show that the underlying contact structure is, up to diffeomorphism, unique. (2000): 53A40, 53C25, 53D10. Mathematics Subject Classification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…For a 3-dimensional CR-manifold M , not isomorphic to a sphere, the Sasakian metric is unique, hence the corresponding cone is also unique. Theorem 1.2 and Theorem 1.3 in dimension 3 follow immediately from [Be1], [Be2]. In this paper, we shall always assume that dim M 5.…”
Section: Sasakian Manifolds and Algebraic Conesmentioning
confidence: 98%
See 1 more Smart Citation
“…For a 3-dimensional CR-manifold M , not isomorphic to a sphere, the Sasakian metric is unique, hence the corresponding cone is also unique. Theorem 1.2 and Theorem 1.3 in dimension 3 follow immediately from [Be1], [Be2]. In this paper, we shall always assume that dim M 5.…”
Section: Sasakian Manifolds and Algebraic Conesmentioning
confidence: 98%
“…In dimension 3, F. A. Belgun has shown that all Sasakian manifolds are obtained this way (see [G], [Be1], [Be2]): Theorem 1.10. A strictly pseudoconvex, compact CR-manifold M of dimension 3 admits a Sasakian metric if and only if M is isomorphic to a U (1)-fibration associated with a positive line bundle on a projective orbifold (Example 1.9).…”
Section: Sasakian Geometry and Contact Geometrymentioning
confidence: 99%
“…Let N 3 be a complete, simply-connected Sasakian 3-manifold. When N is compact, or more generally when N is co-compact in the sense that there is a compact subset K ⊆ N and a group Γ of isometries of N preserving the Sasakian structure such that the union of h(K) for all h ∈ Γ covers N , then N is classified by Belgun [4], [5], [6]. In particular, it was shown in [6,Theorem 4.5] that after the so-called parallel modification, N 3 can be deformed to one of three standard Lie groups with left invariant Sasakian structures: SU (2), SL(2, C), and N il 3 .…”
Section: It Follows Thatmentioning
confidence: 99%
“…endowed with a constant curvature metric; see e.g. [5] or [20 by isospectrality of P * P and P P * except on kernels. The only remaining term here has to be a constant, while we have a t −1/2 in (5.41).…”
Section: Annales De L'institut Fouriermentioning
confidence: 99%